Mixed and disseminated paracoccidioidomycosis after liver transplantation: Case report - Sinkos, Camila (Med Mycol Case Rep, 2021)
Paracoccidioidomycosis (PCM) is a systemic granulomatous fungal infection rarely associated with solid organ transplantation. We report the second case of PCM in an adult after liver transplantation. A 47-year-old woman who had undergone liver transplantation was hospitalized for flu-like symptoms and multiple erythematous ulcerated skin papules. There was lymphadenopathy, pulmonary compromise, and quickly progression to septic shock. PCM was confirmed by skin biopsy and serologic tests, and a satisfactory response to amphotericin B was achieved.